PERAN POLIMORFISME GEN MATRIKS METALLOPROTEINASE-9 DENGAN KEJADIAN PENYAKIT PARU OBSTRUKTIF KRONIK - Wilson Arthur Zein; Yahwardiah Siregar; Amira P Tarigan (Fakultas Keperawatan dan Fisioterapi Institut Kesehatan Medistra Lubuk Pakam, 2020)
Excessive secretion of MMP-9 is one of the cause of COPD is which can cause undesirable lung tissue degradation. Increased expression of MMP-9 is associated with increased gene promoter activity. The purpose of this study was to determine the role of mettaloproteinase-9 matrix gene polymorphisms with COPD events. This was a case-control study. With a total sample of 60 patients consisting of 30 COPD patients and 30 non-COPD patients. Samples were amplified by PCR (Polymerase Chain Reaction) The results of DNA amplification were digested with SphI restriction enzyme to see the allele variant of MMP-9 C-1562T. Visualization of restriction results with 2% agarose gel electrophoresis will show 2 bands on the T allele (188bp, 247bp), 1 band on the C allele (435bp). The results obtained were homozygous CC variants in COPD 20 (66.67%) and non-COPD 21 (70%). Heterozygous variant of CT 10 (33.33%) in COPD and 9 (30%) in non-COPD. TT variant is not found at all. Based on the results obtained by the most CC homozygous variants in COPD (66.67%) and non-COPD (70%) and no association was found between MMP-9 polymorphism and COPD events (p> 0.05). Based on the results of this study, there is no significant relationship that we can conclude.